A Comparative Analysis of Factors Influencing Spectatorship of Disability Sport: A Qualitative Inquiry and Next Steps - Michael Cottingham; Brian Gearity; Andrew Goldsmith; Wonyoung Kim; Matt Walker (Journal of Applied Sports Management, 2015)
To effectively market a sport event, it is necessary to determine the factors that influence spectator attendance. While a developed line of inquiry exists on the marketing of able-bodied sports, a gap in the literature exists in the disability sport context. Thus, there is a need to examine the synergy between existing motives that have been confirmed in traditional sport versus those that are unique to disability sport. This line of inquiry will help future researchers determine whether additional factors should be considered when marketing disability sport. The purpose of this study was to qualitatively explore the explicit and tacit motives of spectator attendance at disability sport. Findings from the Quad Rugby Nationals indicate that while some of the traditional sport spectator motives in the literature are the same, there are also unique motives, which should be used to accurately measure spectator interest in this emerging context.
Keywords: disability; disability sport; sport marketing; sport promotion; consumer behavior